The effect of TSLP, IgE and Eosinophil on Atopic Dermatitis Patients - Jassim, Abbas A.; Al-Kazaz, Abdul Karim A. (Iraqi Journal of Science, 2023)
Atopic dermatitis in another word Atopic Eczema is a chronic inflammatory skin disease that effecting all ages, described by lesions of eczematous and acute itch. As the objective of this study for determine the effect of variation in TSLP, IgE, and Eosinophil levels in patients with atopic dermatitis compared with a healthy control group. The level of TSLP was almost the same between the patients and the control group, and the reason was that most of the patients were treated with anti-allergic drugs. In this study, there is a significant (P = 0.004), serum level of TSLP in atopic dermatitis patient’s pre-treatment with immunotherapy (corticosteroids and antihistamines) is compared with atopic dermatitis patients’ post-treatment with immunotherapy and controls (23.06 vs. 29.48 and 23.99 pg/ml). The median level of overall T-IgE of the Atopic Dermatitis group was substantially greater than controls, (91.64 vs. 49.72 IU/ml), (P<0.023). Eosinophils count of Atopic Dermatitis patients was approximately equal to the control group, (3.1 ± 2.43 vs. 2.9 ± 1.05 %), (P-value 0.07). This study was conducted on a case series of 60 patients that have Atopic Dermatitis, who volunteered due to their review of the Allergy Center in Al-Rusafa, Baghdad, during the fall of 2020. Thirty healthy and non-Atopic Dermatitis volunteers of the same type, the center volunteered as a control group.